(untitled) (Ameghiniana, 2014)
Well preserved braehiopods of Early Caradocian age are reported from boulders contained in the glaeigenie diamictite of the Don Braulio Formation, which probably came from the underlying La Cantera Formation. The fauna is eomposed by the new speeies Aegiromena glacialis, plus Howellites ef. macrostoma (Barrande), Dinorthis sp., Hesperorthis sp., Drabovia? sp., Anchoramena’l sp., and undetermined Leptestiinae and Glyptorthinae. This brachiopod assoeiation shows close affinities with the Mediterranean Aegiromena-Drabovia Fauna of south Europe and Morocco and supports a strong palaeogeographic eonneetion between the Precordillera Terrane and Gondwana sinee the Caradocian.